Numismatic letterforms of ‘A’ in medieval Europe: A classification system - Spenciner, David B.; Spenciner, Marina V. (KOINON: The International Journal of Classical Numismatic Studies, 2019)
Prior study of medieval Latin alphabet letterforms has primarily been the product of epigraphy, and paleography, likely due to their availability to researchers resulting from the durability of the stone and parchment, respectively. With large surface areas on which to work, impressively styled letters could be devised. This may be contrasted with the medieval die cutters who were tasked with generating inscriptions on coins. Generally speaking, the dies (and resulting coins) of this time period were relatively small—10 to 30 mm in diameter and the individual letters even smaller (often less than 3 mm tall). Letterforms can provide context as to the writer’s geography, chronology, and culture.